PEMAHAMAN HADIS-HADIS RUKYAT HILAL DAN RELASINYA DENGAN REALITA ISBÂT RAMADHAN DI INDONESIA - Muhamad Rezi (Institut Agama Islam Negeri (IAIN) Bukittinggi, 2016)
It has become customary that every Muslim anywhere in the world are obliged to fast during Ramadan. One of the annual problems that always appear at the Ramadan is the determination of the beginning and end of Ramadan by sighting the moon. On the orders of the Prophet Muhammad, the determination of Ramadan should be done at the end of the month of Sha'ban. The beginning and end of Ramadan is determined by the appearance of the crescent moon. Such activity is known by rukyat hilal. In its history, the Prophet explained that the methodology of the determination of the beginning and end of Ramadan is sighting the crescent moon with eyes. If sight is obstructed by natural phenomena such as cloud cover, the day of the month of Sha'ban accomplished to 30 days. Contemporary, classic visual method has been carried out with the use of modern tools. Problems often arise because of differences in the understanding the passages of sunnah related to this. Some considered that the hilal rukyat commanded by the Prophet Muhammad is rukyat fi'liyyah while others considered that it is more accurate to use rukyat 'Ilmiyyah with the arithmetic method of calculation (hisab). In Indonesia, the different interpretation and understanding that always makes a difference in executing the fasting and Idul Fitri.